(untitled) (Journal of the College of Basic Education, 2024)
This research aims to identify "The Impact Tiered Activities Strategy in Analytical Thinking of Intermediate First grade Students in science Subject ". The following null hypotheses was derived:. "There is no statistically significant difference at a significance level of 0.05 between the mean scores of the experimental group students who were taught using the Tiered Activities strategy and the mean scores of the control group students who were taught using the conventional method in the analytical thinking test." The experimental design was chosen with experimental and control groups with a post-test for analytical thinking, The research community consisted of all Intermediate First grade Students in the General Directorate of Education in Baghdad/Rusafa Second. Was selected a purposive sample of 60 students from Safi Ad-Din Al-Hilli Intermediate School for boys and divided equally into the experimental and control groups, with 30 students in each group. The researcher ensured equivalence between the two groups based on the following variables: (chronological age, previous achievement, intelligence, and analytical thinking). This was done during the first semester of the academic year 2022-2023. The researcher selected the science subject taught during the experiment, specifically the second and third chapters from the science textbook for the Intermediate First grade. The researcher formulated behavioral objectives for the topics to be taught, comprising 100 behavioral objectives according to Bloom’s taxonomy levels (knowledge, comprehension, application, analysis, synthesis, evaluation). The researcher prepared 22 daily lesson plans (11 each group) to teach the research groups. A sample of the plans was presented to a group of experts to assess their suitability for Intermediate First grade Students. The researcher personally taught both research groups according to the developed lesson plans.To achieve the research objective, the researcher prepared research instrument, was an analytical thinking test consisting of 20 objective items distributed among five skills: (visual analysis of data, sequential pattern analysis, alternative selection, verbal reasoning, and part-whole relationship). Each item had two alternatives. The face validity of the test was established by presenting it to a group of experts in education, science teaching methods, and psychology. Discrimination power, difficulty index, and effectiveness of incorrect alternatives for each item were calculated using appropriate statistical methods. The reliability was determined using the split-half method, with a pre-correction reliability coefficient of 0.69 and a post-correction reliability coefficient of 0.82.After the completion of the 11-week experimental period, preceded by a one-week pre-experimental period in which the researcher conducted equivalence procedures for the two groups, the research instruments were administered to the main sample. The results were analyzed statistically using the independent samples t-test for two independent samples, examining the variables of analytical thinking. The results indicated that the experimental group, which was taught using the Tiered Activities strategy, outperformed the control group, which was taught using the conventional method, in analytical thinking with an effect size of 0.82. These effect sizes indicate a significant advantage for the experimental group.Based on the research findings, the researcher concluded the following: "Teaching Intermediate First Grade Students using the Tiered Activities strategy had a positive impact on improving their analytical thinking." Based on that, the researcher provided several recommendations and suggestions, which are mentioned in Chapter Four.